2004
DOI: 10.1021/jf048786y
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Physicochemical Function Relationships of Soybean Glycinin at Subunit Levels Assessed by Using Mutant Lines

Abstract: Glycinin is a hexameric protein composed of five kinds of subunits. The subunits are classified into two groups, group I (A1aB1b, A1bB2, and A2B1a) and group II (A3B4 and A5A4B3). We purified four mutant glycinins composed of only group I subunits (group I-glycinin), only group II subunits (group II-glycinin), only A3B4 (A3B4-glycinin), and only A5A4B3 (A5A4B3-glycinin) from mutant soybean lines. The physicochemical properties of these glycinin samples were compared with those of the normal glycinin (11S) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 33 publications
7
47
0
Order By: Relevance
“…Each subunit is composed of an acidic and a basic polypeptide linked by a disulphide bond (Staswick et al, 1981). The five subunits form three groups according to the combination of acid and basic peptides (Maruyama et al, 2004). Subunits Gy1 and Gy5 are considered main epitopes for this protein (Schiller et al, 2014).…”
Section: Identified Allergensmentioning
confidence: 99%
“…Each subunit is composed of an acidic and a basic polypeptide linked by a disulphide bond (Staswick et al, 1981). The five subunits form three groups according to the combination of acid and basic peptides (Maruyama et al, 2004). Subunits Gy1 and Gy5 are considered main epitopes for this protein (Schiller et al, 2014).…”
Section: Identified Allergensmentioning
confidence: 99%
“…The five subunits (A 1a B 2 , A 1b B 1b , A 2 B 1a , A 3 B 4 and A 5 A 4 B 3 ) have been isolated, purified (Staswick et al, 1981;Maruyama et al, 2004) and characterized using amino-terminal amino acid sequence (Moreira, Hermodson, Larkins, & Nielsen, 1979;Staswick et al, 1981). Many works about the polypeptides have been carried out for amino acid sequence analysis (Staswick, Hermodson, & Nielsen, 1984), emulsifying properties of acidic polypeptides (Liu, Lee, & Damodaran, 1999), functional properties of polypeptides with different MW obtained by special methods (Dias et al, 2003), as well as their physicochemical and adhesion properties (Mo, Zhong, Wang, & Sun, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2a-d). However, very low solubility was reported for glycinin at acidic pH and high ionic strength conditions (μ= 0.5) [3,11], which was also reported for cruciferin composed of heteromeric subunits [9,[11][12][13]. The effect of neutral salts, such as NaCl, on ion-protein interactions for 11S globulins (e.g., glycinin) is concentration dependent.…”
Section: Solubilitymentioning
confidence: 98%
“…Therefore, structural, functional, and physico-chemical data obtained from WT cruciferin cannot be related to individual subunit types. Studies on glycinin, the 11S globulin of Glycine max, showed that the subunits A1bB2, A2B1a, A5A4B3, A3B4, and A1aB1b possess distinct structural and physico-chemical properties [3][4][5][6], which are responsive to manipulation through protein engineering [7][8][9][10]. The current understanding of cruciferin subunit structure and function is very limited.…”
Section: Introductionmentioning
confidence: 99%